Gender and the silences of social capital: Lessons from Latin America - Molyneux, Maxine (Development and Change, 2002)
Social capital has entered development policy thinking and practice in Latin America where it converges with the premises of a new development agenda that emerged in the 1990s. Women are often central to the forms of social capital that development agencies are keen to mobilize in poverty relief programmes, but the terms of women’s insertion into these programmes is rarely problematized. This article critically examines the gendered assumptions that govern efforts to build social capital, and explores some of the tensions that have arisen in post-transition Latin America between women’s rights and social capital agendas.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique latine; amériques; approches et analyses; discipline; droits des femmes*; inégalités; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques